Persistence and spacetime - Balashov, Yuri, 1960- (Oxford : Oxford University Press, 2010)
How do material objects persist through time and survive change? Are they three-dimensional entities extended in space, or are they four-dimensional spacetime 'worms'? Balashov shows how the theory of relativity supports four-dimensionalism and in so doing illuminates a wide range of metaphysical issues.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Space and time; Special relativity (Physics); Generalized spaces